Dinamika Pendidikan Islam: Antara Kearifan Tradisi, Perubahan Transisi, dan Transformasi Modernisasi - Ridwan, Mohammad; Yanto Maulana Restu (HASBUNA : Jurnal Pendidikan Islam, 2023)
This article discusses the dynamics of Islamic Education within the context of Traditional Wisdom, Transitional Changes, and Modernization Transformation. The research is conducted using a qualitative research method with a literature-based approach. Through analysis and synthesis of relevant literary sources, this article analyzes the significant role of traditional wisdom as the foundation of religious values in Islamic education. Additionally, the article delves into how Islamic educational institutions respond to the challenges of transitional changes triggered by modernization transformation in the era of globalization. By utilizing credible literary sources, this article explores how traditional wisdom and modernization transformation can synergize to shape relevant and meaningful Islamic education for contemporary generations. The findings of this research offer profound insights into the dynamics of Islamic education, as well as provide perspectives on how educational institutions can bridge the gap between tradition and change, and respond to current challenges with appropriate and responsive solutions.